Corrosion resistant conductive geopolymer concrete and method of preparation and electrochemical deposition repair thereof
Patent Information
- Application Number
- CN202610906396.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-23
- Publication Date
- 2026-10-27
AI Technical Summary
[0007]本发明针对地聚合物混凝土收缩易开裂、多孔非均质结构导致电化学修复时电场分布不均、沉积产物与基体粘结差及修复深度浅等技术问题,采用丙烯酸酯共聚乳液与导电填料(如鳞片石墨粉)协同改性地聚合物基体并内置电极网络以构建三维连续导电通路,结合特定浓度锌盐电解液在优化电流密度下进行电化学沉积的技术手段,取得了显著抑制基体收缩开裂、实现电场均匀分布与深层异质成核、原位生成致密且具“微锚固”效应的氧化锌沉积层,从而实现裂缝高效愈合(愈合率100%、填充深度≥20mm)、腐蚀表面高覆盖率(≥95%)及长效抗地下污水腐蚀的技术效果
1.材料层面的协同增强:
Smart Images

Figure CN122977761A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building materials technology, specifically to a corrosion-resistant and conductive polymer concrete and its preparation and electrochemical deposition repair method. Background Technology
[0002] Underground sewage pipes are exposed to a complex corrosive environment, making them susceptible to physical corrosion (water erosion, wet-dry cycles), chemical corrosion (acid and salt corrosion), and microbial corrosion. This often leads to mortar detachment and aggregate exposure on the cement concrete surface of the pipes, and in severe cases, cracking and steel reinforcement corrosion. Geopolymers, as a new type of low-carbon cementitious material, form a three-dimensional network colloidal structure through geopolymer reactions using silicate-alumina raw materials and alkali activators. This structure exhibits superior chemical corrosion resistance compared to silicate cement, making it more advantageous than cement concrete in corrosion control of underground sewage pipes.
[0003] However, geopolymer concrete still faces unresolved technical challenges in practical applications and service life: First, there are inherent performance defects in the material itself: geopolymers have a high shrinkage rate, making them prone to microcracks and even macroscopic cracks. These cracks can become rapid entry channels for corrosive media, weakening their corrosion resistance. To overcome this defect, existing technologies have attempted to modify geopolymers with organic polymer emulsions to increase toughness and crack resistance, such as using styrene-acrylic emulsions. However, such modifications often come at the cost of sacrificing some of the material's density or long-term chemical stability, and there is little specific optimization for the complex environment of underground wastewater (high acidity, high salinity, microorganisms).
[0004] Secondly, there is a mismatch in repair technologies: Electrochemical deposition repair technology, which generates insoluble deposits within cracks, has been proven to effectively repair microcracks in traditional cement concrete. Existing technologies disclose various electrodeposition solutions (such as zinc salt and magnesium salt solutions) and repair devices for cement concrete (such as CN200520076008). However, geopolymer concrete and cement concrete differ fundamentally in their reaction mechanisms, pore solution chemical environment (geopolymers maintain a stable pH of 12-13, and retain a high level even after carbonization), and microstructure (higher porosity and surface charge density). Directly applying electrochemical repair technologies designed for cement concrete to geopolymer concrete presents the following new technical challenges: (1) Deposition efficiency and coverage issues: For large-area corrosion of geopolymer concrete surfaces, higher deposition efficiency and larger surface coverage are required; (2) Uneven electric field distribution: The high porosity and heterogeneous microstructure of geopolymer concrete may lead to uneven electric field distribution, affecting the uniformity and density of the deposited products during the electrochemical repair process. (3) Solution compatibility issues: Electrochemical deposition repair solutions should not cause new chemical corrosion to the polymer concrete; (4) Interface bonding problem: The deposited products form a strong bond with the geopolymer matrix to avoid peeling.
[0005] It is evident that the existing technology lacks a complete technical solution that can both improve the crack resistance and corrosion resistance of polymer concrete from the material source and carry out efficient and uniform electrochemical repair tailored to its own characteristics.
[0006] The information disclosed in this background section is intended only to enhance the understanding of the background technology of this disclosure and should not be construed as an admission or in any way implying that the information constitutes prior art known to those skilled in the art. Summary of the Invention
[0007] This invention addresses the technical problems of geopolymer concrete, such as shrinkage and cracking, uneven electric field distribution during electrochemical repair due to its porous and heterogeneous structure, poor adhesion between the deposited products and the matrix, and shallow repair depth. It employs a technique of synergistic modification of the geopolymer matrix with acrylate copolymer emulsion and conductive fillers (such as flake graphite powder) and an embedded electrode network to construct a three-dimensional continuous conductive pathway. Combined with a zinc salt electrolyte of a specific concentration and electrochemical deposition at an optimized current density, this invention achieves significant results in inhibiting matrix shrinkage and cracking, achieving uniform electric field distribution and deep heterogeneous nucleation, and generating a dense zinc oxide deposit layer with a "micro-anchoring" effect in situ. This results in highly efficient crack healing (100% healing rate, filling depth ≥20mm), high corrosion surface coverage (≥95%), and long-term resistance to underground sewage corrosion.
[0008] The limestone aggregate used in the geopolymer concrete of this invention, whose main component is calcium carbonate, reacts with acidic media in wastewater to reduce the acidity of the concrete surface to a certain extent, consuming the acidic media in the wastewater, protecting the concrete matrix, and reducing the corrosion rate. Furthermore, the addition of an organic modifier enables the concrete to maintain structural integrity in a chemically corrosive environment and form a flexible polymer film that fills capillaries and microcracks, significantly reducing porosity and water absorption, thereby preventing harmful media in wastewater from penetrating into the interior of the concrete specimen. Simultaneously, the organic modifier effectively inhibits crack formation by reducing the elastic modulus, increasing the ultimate tensile strength, and reducing shrinkage deformation, thus enhancing crack resistance and preventing the penetration of harmful media from wastewater due to cracking.
[0009] According to a first aspect of this disclosure, a corrosion-resistant and conductive polymer concrete is provided, comprising the following components per cubic meter of concrete: 400-450 kg of silicon-aluminum raw materials; The alkaline activator, calculated as Na2O, is 4% to 8% of the silicon-aluminum raw material. An organic modifier is added at a dosage of 5% to 20% of the mass of the aluminosilicate raw material. The conductive filler is added at a rate of 2% to 8% of the mass of the aluminosilicate raw material. The total amount of additives is 1% to 3% of the mass of the silicon-aluminum raw materials; Water, the amount used is 148~190 kg, and the water-to-gel ratio is 0.37~0.40; Aggregate, with a sand content of 35%~42%; And an electrode system embedded in the concrete matrix, the electrode system comprising a mesh electrode sheet as an anode and a pre-embedded steel bar as a cathode; The conductive filler is uniformly dispersed in the concrete matrix, forming a three-dimensional continuous conductive network together with the electrode system, and providing heterogeneous nucleation sites for subsequent electrochemical deposition products.
[0010] In some embodiments of this disclosure, the alkaline activator is prepared from sodium hydroxide and water glass, and the modulus of the water glass is made up to 1.0 to 1.5 by controlling the ratio of the two; the silicoaluminous raw material contains active silicon dioxide and alumina minerals, selected from at least one of fly ash, granulated blast furnace slag powder, metakaolin, silica fume, steel slag powder, calcined coal gangue powder, and spontaneously combusting coal gangue powder.
[0011] In some embodiments of this disclosure, the organic modifier is an acrylate copolymer emulsion; the additive is composed of a melamine-based high-efficiency water-reducing agent, boric acid and sodium gluconate, with a mass ratio of (0.8~1.2):(0.8~1.2):(0.18~0.22).
[0012] In some embodiments of this disclosure, the aggregate includes natural river sand and limestone coarse aggregate, the limestone coarse aggregate being used to undergo an in-situ neutralization reaction in an acidic wastewater environment to reduce the acidity of the concrete surface; the conductive filler is flake graphite powder, which overlaps to form a conductive path.
[0013] In some embodiments of this disclosure, the electrode system includes at least two external electrodes and at least two internal electrodes, wherein the external electrodes are 10 mm from both ends of the concrete member / structure, and the internal electrodes are 40 mm from both ends of the concrete member / structure. The mesh electrode sheet is made of titanium mesh, graphite plate or stainless steel mesh; the embedded steel bar is Q235 plain round steel bar with surface polishing treatment.
[0014] According to a second aspect of this disclosure, a method for preparing the corrosion-resistant and conductive geopolymer concrete is provided, comprising the following steps: S1. Weigh the silicon-aluminum raw materials and dry mix them evenly; S2. The organic modifier, conductive filler and water are premixed and then added to the mixture in S1 along with the additive and alkaline activator and stirred. S3. Add the aggregate and continue stirring until homogeneous; S4. Inject the mixture obtained in the previous step into the mold in several batches. When the injection volume reaches 1 / 2 of the mold volume, place the electrode system and fix it. Then fill the mold with the mixture and vibrate to form the shape. S5. After hardening, demold and seal for curing at 25~45℃ until the predetermined age.
[0015] According to a third aspect of this disclosure, an application of the corrosion-resistant conductive polymer concrete described above in the preparation of corrosion-resistant components is provided, wherein the corrosion includes physical corrosion caused by water flow erosion and wet-dry cycles, chemical corrosion caused by acid and salt media, and microbial-induced corrosion.
[0016] According to a fourth aspect of this disclosure, an electrochemical deposition repair method for the corrosion-resistant and conductive geopolymer concrete is provided, comprising the following steps: (1) Insulation treatment: The non-repaired surface of the concrete is sealed and insulated, leaving only the cracks and / or the surface to be repaired exposed; (2) Electrolyte immersion: Immerse the crack and / or the surface to be repaired in an electrochemical deposition solution, wherein the electrochemical deposition solution is a zinc salt solution with a concentration of 0.05~0.15 mol / L; (3) Electric field application: Apply a DC voltage between the anode and cathode of the electrode system, and control the current density to be between 0.5 and 1.5 A / m. 2 Within the specified range, maintain for a certain period of time; (4) Solution maintenance: The electrochemical deposition solution is replaced periodically during the repair process to maintain the concentration; wherein, the highly alkaline environment of the pore liquid of the concrete matrix and the heterogeneous nucleation sites provided by the conductive filler are used to drive zinc ions to be electrodeposited in situ inside the crack and on the corrosion surface to form a dense zinc oxide deposition layer, forming a micro-anchoring structure.
[0017] In some embodiments of this disclosure, the zinc salt solution is a zinc sulfate solution or a zinc nitrate solution.
[0018] In some embodiments of this disclosure, the periodic replacement refers to replacing the solution every 3 to 7 days; the maintenance period is 14 to 28 days.
[0019] One or more technical solutions provided in the embodiments of this application have at least one of the following technical effects or advantages: 1. Synergistic enhancement at the material level: ① Improved Crack Resistance and Corrosion Resistance: This invention incorporates a specific proportion of organic polymer emulsion (such as acrylate copolymer emulsion). On one hand, this emulsion forms a flexible polymer film within the geopolymer gel pores and microcracks, effectively filling capillaries, reducing porosity and water absorption, and physically blocking the penetration of harmful media in wastewater. On the other hand, it significantly inhibits the generation and propagation of cracks by reducing the elastic modulus and shrinkage deformation. The high chemical bond energy between this film and the geopolymer matrix itself forms a rigid-flexible protective system, ensuring that the compressive strength remains above 50 MPa after corrosion, with a mass loss of less than 1.0% and a corrosion depth of less than 0.1 mm.
[0020] ② Adaptation of Conductive Functionalization to Electrochemical Remediation: This invention creatively incorporates a specific proportion of conductive filler (such as flake graphite powder) into the geopolymer, which is uniformly distributed in the matrix to form a continuous conductive pathway. This is not merely a simple imparting of conductivity, but effectively solves key obstacles in the use of organically modified geopolymers for electrochemical remediation: ① Improved Electric Field Uniformity: Significantly reduces matrix resistivity (by 2-3 orders of magnitude), resulting in a more uniform electric field distribution during electrochemical remediation, thereby ensuring the uniformity and density of the deposited product (surface coverage exceeding 95%); ② Provision of Nucleation Sites: The abundant active sites on the graphite surface serve as heterogeneous nucleation cores for the deposited product, guiding zinc oxide to grow uniformly on and inside the crack surface, avoiding the defect of deposits only accumulating on the surface in traditional remediation (crack filling depth exceeding 20 mm).
[0021] 2. Improved compatibility at the repair method level: (1) Targeted Deposition Optimization for Geopolymer Environments: The zinc salt (zinc sulfate / zinc nitrate) solution selected in this invention is used for electrochemical deposition at specific concentrations and current densities. The resulting zinc oxide deposits exhibit good compatibility with the geopolymer matrix: ① "Micro-anchoring" effect: Zinc oxide can penetrate into the pores of the geopolymer, forming a physical interlocking bond, resulting in a strong adhesion and solving the problem of deposit product peeling; ② Environmental tolerance: As an amphoteric oxide, zinc oxide has strong chemical inertness and excellent corrosion resistance in underground wastewater (acid / salt environment with pH=4). More importantly, during the electrochemical remediation process of the geopolymer, the OH- produced by the cathode reaction... - This further enhances the already stable (pH>12) alkaline environment of the pore solution, unlike cement concrete where the pH value drops rapidly due to calcium ion loss. This unique chemical environment compatibility ensures the continuity of the repair process and the long-term stability of the repaired interface.
[0022] (2) Through the combined effect of materials and methods, synergistic, efficient and uniform repair of corroded surfaces (coverage > 95%) and internal microcracks (healing rate 100%, filling depth > 20 mm) was achieved. Attached Figure Description
[0023] Figure 1 This is an elemental distribution diagram of the graphite-doped geopolymer obtained in Example 1 of this application.
[0024] Figure 2 This is a microscopic morphology diagram of the organically modified geopolymer obtained in Example 1 of this application. Detailed Implementation
[0025] Unless otherwise specified, the instruments and equipment involved in the following embodiments are all conventional instruments and equipment; the industrial raw materials involved are all commercially available conventional industrial raw materials; and the processing and manufacturing methods involved are all conventional methods unless otherwise specified.
[0026] To better understand the technical solution of this application, the above technical solution will be described in detail below with reference to the accompanying drawings and specific embodiments.
[0027] The process of simulating the corrosion of the specimen was as follows: a flexural testing machine was used to flex the specimen to create a through crack with a width of 0.5 mm; the four sides of the geopolymer concrete specimen (except the two sides through which the crack penetrated) were sealed with epoxy resin to make it insulated; the specimen was immersed in sewage (sodium sulfate and sodium chloride concentrations of 500 mg / L, magnesium sulfate concentration of 50 mg / L, sodium acetate concentration of 30 mg / L, and the pH value was adjusted to 4 with sulfuric acid) for 56 days.
[0028] Example 1: Preparation and Simulated Repair Test Verification of Geopolymer Concrete This example discloses the preparation of conductive geopolymer concrete resistant to underground pipeline sewage corrosion and its electrochemical deposition repair method, which is carried out according to the following steps: S1. Preparation of alkaline activator: The alkaline activator is prepared by NaOH and water glass, and the modulus is controlled to be 1.4; the activator dosage is controlled according to Na2O accounting for 6% of the silicon-aluminum raw materials; after mixing evenly, it is stored at room temperature; S2. Dry mixing: Weigh out 440 kg / m³ of silicoaluminous raw materials (fly ash, metakaolin, and slag powder in a mass ratio of 0.2:1:1). 3 Mix dry for 2 minutes using a forced mixer; S3. Wet mixing: Mix acrylate copolymer emulsion (10% admixture), flake graphite powder (5% admixture), and water (176 kg / m³). 3 The mixture (water-cement ratio 0.40) is premixed and then added to S2 along with additives (melamine-based high-efficiency water-reducing agent, boric acid and sodium gluconate at 1.0%, 1.0% and 0.2% of the silica-alumina raw material, respectively) and alkaline activator, and stirred for 1 min. S4. Add aggregate: Add natural river sand and 5~25mm limestone coarse aggregate (sand ratio 38%), and mix for another 2 minutes using a forced mixer; S5. Molding and Electrode Placement: Pour the well-mixed geopolymer concrete into the specimen mold. When the amount added reaches half the volume of the mold, add four 304 stainless steel mesh electrode sheets (pore diameter 3.5mm×3.5mm, single wire diameter 0.8mm, two outer electrodes 10mm away from both ends of the specimen, two inner electrodes 40mm away from both ends of the specimen), and fix the electrode sheets with clamps. Then pour in concrete, place it on the vibrating table, and fully vibrate and shape it. S6. Cathode placement: Pre-embed 6mm diameter, polished smooth Q235 round steel bars as cathodes; S7. Curing: After curing for 24 hours, demold to prepare a geopolymer conductive specimen, and cure under sealed curing conditions at 30℃ for 28 days.
[0029] S8. Precast crack: A 0.5 mm wide through crack is observed during the flexural test.
[0030] S9. Insulation: Except for the crack and the surface to be repaired, the other four sides are sealed with epoxy resin.
[0031] S10. Corrosion: Immersed in simulated wastewater (containing 500 mg / L sodium sulfate, 500 mg / L sodium chloride, etc.) at pH=4 for 56 days.
[0032] S11. Electrochemical remediation: Immerse in 0.10 mol / L zinc sulfate solution, apply direct current, and control the current density at 1.0 A / m. 2 The treatment lasted 28 days, with the solution changed every 5 days during this period.
[0033] After completion, the surface coverage, permeability, crack healing rate, and crack filling depth were measured.
[0034] Examples 2-4: The basic steps are the same as in Example 1, and the specific parameter adjustments are shown in Table 1 below.
[0035]
[0036] Comparative Example 1 (lacking conductive filler / graphite) The only difference from Example 1 is that flake graphite powder is not added, and quartz powder of equal mass is used instead to maintain consistent volume.
[0037] Comparative Example 2 (lacking organic modifier) The only difference from Example 1 is that no acrylate copolymer emulsion is added, and an equal mass of water is used instead.
[0038] Comparative Example 3 (replaced with traditional cement-based electrolyte) The only difference from Example 1 is that the electrochemical deposition repair solution is replaced with a calcium nitrate solution of the same concentration (0.10 mol / L), and the other parameters are the same as in Example 1.
[0039] Comparative Example 4 (replaced with conventional silicate cement matrix) The only difference from Example 1 is that ordinary Portland cement (PO 42.5, 440 kg / m³) is used. 3 The alternative is a polymeric aluminosilicate raw material and an alkaline activator, without the addition of graphite and acrylate copolymer emulsion, and the rest (electrode, zinc salt repair) are the same as in Example 1.
[0040] Comparative Example 5 (without built-in electrode network) The only difference from Example 1 is that no mesh electrode sheet and steel cathode are pre-embedded during concrete pouring, and temporary electrodes are only attached to the surfaces at both ends of the crack during repair.
[0041] Performance testing and results analysis: The specimens prepared in Examples 1-4 and Comparative Examples 1-5 were subjected to performance tests. The test methods were in accordance with relevant national and industry standards, and the results are shown in Table 2 below.
[0042]
[0043] from Figure 1 As can be seen, the added graphite, evenly distributed in the geopolymer, can form a continuous conductive path in the geopolymer concrete, reducing the resistivity by 2-3 orders of magnitude and effectively enhancing the depth of electrochemical repair. The addition of graphite improves the overall conductivity of the system and the uniformity of the electric field distribution, leading to increased uniformity and density of the deposited products. Graphite's excellent electronic conductivity reduces ohmic losses in the electrochemical system, increasing the current density under the same voltage and accelerating the deposition reaction rate. Graphite does not corrode or leach metal ions in alkaline electrolyte environments, avoiding secondary pollution or performance degradation that may occur with traditional metal electrodes, ensuring the stability of the electric field distribution during long-term repair. The abundant active sites on the graphite surface can serve as heterogeneous nucleation cores for the deposited products, enabling uniform growth of the deposited products on and inside the cracks, avoiding the defects of traditional repairs where the deposited layer only accumulates on the surface and has a low internal filling rate. The bridging effect of graphite can improve the tensile strength and toughness of concrete.
[0044] Comparing Example 1 and Comparative Example 1, it can be seen that after removing graphite powder, although there are still pre-embedded electrodes, the crack filling depth drops sharply from 21 mm to 6 mm, and the surface coverage drops from 97% to 65%. This conclusively proves that graphite powder not only reduces the matrix resistance, but its abundant surface active sites are also heterogeneous nucleation cores for ZnO deposition, guiding the deposits to grow deeper into the cracks, rather than just accumulating on the surface.
[0045] from Figure 2 As can be seen, when acrylate copolymer emulsion is incorporated into geopolymer, it can form a flexible polymer film that fills capillary pores and microcracks, significantly reducing porosity and water absorption, thereby preventing harmful media in sewage from penetrating into the interior. By reducing the elastic modulus, increasing the ultimate tensile strength, and reducing shrinkage deformation, acrylate copolymer emulsion effectively inhibits crack formation, thereby enhancing crack resistance and preventing harmful media in sewage from penetrating due to cracking.
[0046] Comparing Example 1 and Comparative Example 2, it can be seen that the lack of acrylate copolymer emulsion modification led to a surge in the initial crack area (from 0.07% to 0.42%), indicating that the organic flexible film formed by the acrylate copolymer emulsion plays an irreplaceable role in sealing capillaries and inhibiting shrinkage cracking, providing a good substrate for subsequent electrochemical repair.
[0047] Comparing Example 1 with Comparative Example 3 (using conventional calcium salts), it can be seen that in the highly alkaline environment of geopolymers, calcium ions cannot form dense deposits, and the crack healing rate is only 30%; while Example 1, which uses zinc salts, achieves a healing rate of 100%. This shows that the present invention overcomes the technical prejudice that "concrete electrochemical repair must rely on calcium salts" and cleverly utilizes the highly alkaline environment of geopolymers to promote zinc salt deposition.
[0048] Comparing Example 1 with Comparative Example 4 (ordinary cement matrix), it can be seen that ordinary cement undergoes severe decalcification and deterioration (mass loss of up to 4.6%) under the combined effects of sewage and electric field, while the geopolymer matrix only loses 0.5% of its mass.
[0049] Comparing Example 1 and Comparative Example 5, it can be seen that without the built-in electrode network, the electric field only acts on the surface, and the filling depth is only 8 mm. This proves that the three-dimensional conductive system of the present invention, consisting of "matrix conductive filler + built-in electrode network," is a guarantee for achieving deep repair.
[0050] Although some preferred embodiments of the invention have been described, those skilled in the art, upon learning the basic inventive concept, can make other changes and modifications to these embodiments. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments as well as all changes and modifications falling within the scope of the invention.
[0051] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, this application is also intended to include such modifications and variations if they fall within the scope of the claims of this application and their equivalents.
Claims
1. A corrosion-resistant and conductive polymer concrete, characterized in that, Per cubic meter of concrete, it includes the following components: 400-450 kg of silicon-aluminum raw materials; The alkaline activator, calculated as Na2O, is 4% to 8% of the silicon-aluminum raw material. An organic modifier is added at a dosage of 5% to 20% of the mass of the aluminosilicate raw material. The conductive filler is added at a rate of 2% to 8% of the mass of the aluminosilicate raw material. The total amount of additives is 1% to 3% of the mass of the silicon-aluminum raw materials; Water, the amount used is 148~190 kg, and the water-to-gel ratio is 0.37~0.40; Aggregate, with a sand content of 35%~42%; And an electrode system embedded in the concrete matrix, the electrode system comprising a mesh electrode sheet as an anode and a pre-embedded steel bar as a cathode; The conductive filler is uniformly dispersed in the concrete matrix, forming a three-dimensional continuous conductive network together with the electrode system, and providing heterogeneous nucleation sites for subsequent electrochemical deposition products.
2. The corrosion-resistant and conductive polymer concrete according to claim 1, characterized in that, The alkaline activator is prepared from sodium hydroxide and water glass, and the modulus of the water glass is made up to 1.0 to 1.5 by controlling the ratio of the two. The silica-alumina raw material contains active silica and alumina minerals, selected from at least one of fly ash, granulated blast furnace slag powder, metakaolin, silica fume, steel slag powder, calcined coal gangue powder, and self-igniting coal gangue powder.
3. The corrosion-resistant and conductive geopolymer concrete according to claim 1, characterized in that, The organic modifier is an acrylate copolymer emulsion; the additive is composed of melamine-based high-efficiency water-reducing agent, boric acid and sodium gluconate, with a mass ratio of (0.8~1.2):(0.8~1.2):(0.18~0.22).
4. The corrosion-resistant and conductive polymer concrete according to claim 1, characterized in that, The aggregates include natural river sand and limestone coarse aggregates. The limestone coarse aggregates are used to undergo an in-situ neutralization reaction in an acidic wastewater environment to reduce the acidity of the concrete surface. The conductive filler is flake graphite powder, which overlaps to form a conductive path.
5. The corrosion-resistant and conductive polymer concrete according to claim 1, characterized in that, The electrode system includes at least two external electrodes and at least two internal electrodes, wherein the external electrodes are 10 mm away from both ends of the concrete component / structure, and the internal electrodes are 40 mm away from both ends of the concrete component / structure. The mesh electrode sheet is made of titanium mesh, graphite plate or stainless steel mesh; the embedded steel bar is Q235 plain round steel bar with surface polishing treatment.
6. A method for preparing corrosion-resistant and conductive geopolymer concrete as described in any one of claims 1-5, characterized in that, It includes the following steps: S1. Weigh the silicon-aluminum raw materials and dry mix them evenly; S2. The organic modifier, conductive filler and water are premixed and then added to the mixture in S1 along with the additive and alkaline activator and stirred. S3. Add the aggregate and continue stirring until homogeneous; S4. Inject the mixture obtained in the previous step into the mold in several batches. When the injection volume reaches 1 / 2 of the mold volume, place the electrode system and fix it. Then fill the mold with the mixture and vibrate to form the shape. S5. After hardening, demold and seal for curing at 25~45℃ until the predetermined age.
7. The application of corrosion-resistant conductive polymer concrete as described in any one of claims 1 to 5 in the preparation of corrosion-resistant components, wherein the corrosion includes physical corrosion caused by water flow erosion and wet-dry cycles, chemical corrosion caused by acid and salt media, and microbial-induced corrosion.
8. A method for electrochemical deposition repair of corrosion-resistant and conductive geopolymer concrete as described in any one of claims 1 to 5, characterized in that, It includes the following steps: (1) Insulation treatment: The non-repaired surface of the concrete is sealed and insulated, leaving only the cracks and / or the surface to be repaired exposed; (2) Electrolyte immersion: Immerse the crack and / or the surface to be repaired in an electrochemical deposition solution, wherein the electrochemical deposition solution is a zinc salt solution with a concentration of 0.05~0.15 mol / L; (3) Electric field application: Apply a DC voltage between the anode and cathode of the electrode system, and control the current density to be between 0.5 and 1.5 A / m. 2 Within the specified range, maintain for a certain period of time; (4) Solution maintenance: The electrochemical deposition solution is replaced periodically during the repair process to maintain the concentration; wherein, the highly alkaline environment of the pore liquid of the concrete matrix and the heterogeneous nucleation sites provided by the conductive filler are used to drive zinc ions to be electrodeposited in situ inside the crack and on the corrosion surface to form a dense zinc oxide deposition layer, forming a micro-anchoring structure.
9. The electrochemical deposition remediation method according to claim 8, characterized in that, The zinc salt solution is a zinc sulfate solution or a zinc nitrate solution.
10. The electrochemical deposition remediation method according to claim 8, characterized in that, The term "regular replacement" refers to replacing the solution every 3 to 7 days; the term "maintaining for a certain period of time" refers to 14 to 28 days.
Citation Information
Patent Citations
Apparatus for modification of concrete crack by electrochemical deposition
CN2861375Y